2021
DOI: 10.3390/molecules26134001
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Performance of Two Extraction Solvent Systems on Phenolic Constituents from U.S. Southeastern Blackberries

Abstract: Two common extraction solvent systems, namely acidified aqueous methanol and acidified aqueous acetone, were used to extract blackberry phenolics, and the antioxidant properties of the recovered extracts were compared. The crude extracts were fractionated into low- and high-molecular-weight phenolics by Sephadex LH-20 column chromatography. The hydrophilic-oxygen radical absorbance capacity (H-ORACFL), ferric reducing antioxidant power (FRAP), and the cellular antioxidant activity (CAA) assays were employed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Prior to the HPLC analysis, an extraction solvent with acetone, ultrapure water, and acetic acid (70:29.50:0.50 v/v/v) was made (Liao et al, 2021). Then, equal volumes of the optimized hibiscus extract and extraction solvent were mixed, being afterward subjected to the chromatographic separation at 30 • C and 0.65 mL/min.…”
Section: Hplc and Uhplc Analyses Of The Hibiscus Extractmentioning
confidence: 99%
“…Prior to the HPLC analysis, an extraction solvent with acetone, ultrapure water, and acetic acid (70:29.50:0.50 v/v/v) was made (Liao et al, 2021). Then, equal volumes of the optimized hibiscus extract and extraction solvent were mixed, being afterward subjected to the chromatographic separation at 30 • C and 0.65 mL/min.…”
Section: Hplc and Uhplc Analyses Of The Hibiscus Extractmentioning
confidence: 99%
“…In addition, Liao et al . (2021) used an acidified methanol aqueous solution and acidified acetone aqueous solution to extract phenolic compounds from the blackberry. It was found that the methanol solvent system was more efficient in extracting anthocyanins from the blackberry.…”
Section: Solid‐liquid Extractionmentioning
confidence: 99%